Qualitative Analysis Of The San Lorenzo Landslide In The Sant' Arcangelo Region Southern Italy - Muh Aris Marfai; Graciela Peters Guarin; Fransisco De La Caridad Viera Cepero (Indonesian Journal of Geography, 2006)
This study is applying qualitative analysis based on the multitemporal evidence for generating the expected-landslide hazard map. The study was carried out in San Lorenzo area, Sant' Arcangelo, Southern Italy. The main objectives of this study are: 1) to identify and generate old-landslide map year 1976 and recent-landslide map year 2002, and 2) to generate the expected hazard map based on multitemporal evidence. Interpretation of the aerial photographs has been used to determine the type of landslide and landslide activity in 1976, and fieldwork has been done to check type, of landslide and to determine the landslide activity in 2002. The comparison between activity 1976 and 2002 have been done in order to generate the expected hazard map. Most of the active landslide in 1976 and 2002 are complex and rockfalls type and only small part are spread; slide and flow. Some active landslides in 1976 are still active in 2002 and even inactive landslides in 1976 become active in 2002 and leading to the extended high and moderate hazard area.